ANALISIS TINGKAT KEPUASAN PELANGGAN RUMAH TANGGA TERHADAP PERUSAHAAN DAERAH AIR MINUM (PDAM) DI WILAYAH PRUMNAS NENDAGUNG KOTA PAGAR ALAM - Ryian Shaputra; Fameira Dhiniati; Barrorotul Azizah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
The availability of clean water is highly expected by the community to support their daily activities, ideal clean water must be clear, colorless, tasteless, odorless, without germs and all living things that endanger human health that come from wells, surface springs, rivers and services of the Regional Drinking Water Company. The purpose of this study was to determine the level of household customer satisfaction with the Pagar Alam Municipal Drinking Water Company in the Perumnas Nendagung area. With 542 active subscribers, the service quality is still not optimal, especially in the Perumnas Nendagung area. As for data collection, a questionnaire was carried out to 85 PDAM customers in the Perumnas Nendagung area randomly. For research data processing using the Importance and Performance Analysis (IPA) method, the Customer Satisfaction Index (CSI). From the results of research, clean water treatment is the most important priority for improvement and from the results of the research, the overall customer assessment of product quality and service quality can be said to be quite satisfied with the CSI score of 0.6335 for product quality and 0.6357 for service quality.